Pengenalan dan Pengendalian Hama Ulat Grayak Frugiperda (Spodoptera frugiperda) di Desa Bonjor, Kabupaten Rembang - Dewi Sartiami; Paryoto Paryoto; Hajrian Rizqi Albarki; Zulianah Saputri; Kiki Sari; Nur Sa’adha; Nifa Khalidah; Sofi Illiyin; Za’immatul Mu’allimah; Nailul Ianah (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2023)
Indonesian farmers are now facing a new challenge of a recently emerging pest problem. Early in 2019, farmers in Indonesia were threaten by a massive attack of fall armyworm that caused severe damage to their corn crops. According to students of Thematic Student Study Service (KKN-T) 2021 assigned in Bonjor Village, Rembang Regency, fall armyworms have been making their presence known in that area. Farmers did not recognized fall armyworm before, but they had suspected a pest was the one causing damage to their crops. Introducing the fall armyworm to farmers and their management using natural enemies are the core purposes of this study. The study was carried out by conducting a pre-test on farmers in advance, webinar and training then proceeded with a post-test. The tests were run on 21 farmers in Bonjor Village, Rembang Regency. The majority of farmers in Bonjor have less than 5 years of farming experience, a farm less than 2 ha, and crop production below 5 tons/ha. All farmers claimed that their crops were damaged by UGF attacks. Farmers' knowledge of UGF before the training was only 5% while after the training increased to 43%. Farmers became more familiar with Spodoptera frugiperda pests and other pests. Farmers' understanding of egg groups is still low. Farmers know how to control armyworm frugiperda by utilizing parasitoids and the role of parasitoid roofs.